In defense of the public space - Montaner, Josep Maria (2021)
This article analyzes conceptually and historically the meaning of public space, defending its growth and arguing the dangers of when it is reduced and tends to disappear. Alternatives for pedestrianization and renaturation are presented, especially those recently applied in Barcelona and other Catalan cities.